Pendalaman Konsep Dalam Rangka Persiapan Kompetisi Bidang Statistika Untuk Siswa Sma Negeri 2 SBB - Salhuteru, Rosalina; Lembang, Ferry Kondo; Haumahu, G.; Nanlohy, Y. W. A.; Laamena, Novita S.; Yudistira, Yudistira (PENGAMATAN: Jurnal Pengabdian Masyarakat untuk Ilmu MIPA dan Terapannya, 2024)
Statistics taught at high school level consists of several basic concepts, namely descriptive statistics, combinatorics, and probability theory. Competitions can be an effective tool to encourage students to hone their skills and assess the extent to which the concepts they have learned are applied well. However, until now there is still a gap in student achievement in competitions between Maluku Provinces, due to gaps in students' understanding of basic concepts, especially in the field of Statistics. SMA Negeri 2 Seram Barat, as one of the leading schools in the region, actually has the potential to encourage its students to excel in competitions, but is hampered by an understanding of basic concepts, especially in the field of Statistics, which is still not optimal. The Mathematics Department, Faculty of Mathematics and Natural Sciences, Pattimura University took the initiative to provide deeper concepts to students at SMA Negeri 2 West Seram as preparation for facing competitions in the field of statistics, by providing effective explanations of the basic concepts of statistics that have been studied at the high school level, as well as enriching them with practice questions at Olympic level. to encourage students to work on questions. This activity aims to help students at SMA Negeri 2 Seram Barat Part in understanding the basic concepts in the field of Statistics, as well as as an example for SMA Negeri 2 Seram Barat teachers in implementing more effective student development strategies in order to prepare for competitions in the field of Statistics that will be participated in in the future. will come.